Trajectory planning for unmanned surface vehicles operating under wave-induced motion uncertainty in dynamic environments. (25th November 2020) - Rajendran, Pradeep; Moscicki, Travis; Wampler, Jared; Ellenrieder, Karl von; Gupta, S. K.
We present a deliberative trajectory planning method to avoid collisions with traffic vessels. It also plans traversal across wavefields generated by these vessels and minimizes the risk of failure. Our method searches over a state-space consisting of pose and time. And, it produces collision-free and minimum-risk trajectory. It uses a lookup table to account for motion uncertainty and failure risk. We also present speed-up techniques to increase performance. Our wave-aware planner produces plans that (1) have shorter execution times and safer when compared to previously developed reactive planning schemes and (2) comply with user-defined wave-traversal constraints and Collision Regulations (COLREGs)